The Special Autonomy Funds are not for Poverty Alleviation: A lesson from Aceh's Way - Ikhsan; Vellayati Hajad; Nodi Marefanda; Akmal Saputra; Herizal (Universitas Muhammadiyah Malang, 2022)
This article is about the Allocation of the Special Autonomy Fund's efforts to combat poverty in Aceh. The Special Autonomy Fund began in 2008 and will continue until 2027, with the goal of achieving the highest level of peace in Aceh. Data is derived from interviews and supporting documents from the Bappeda Aceh and the Indonesian Ministry of Finance, as well as a quantitative method based on case studies. Following that, data is analyzed through the methods of display, reduction, and data analysis. The findings indicate that the Aceh Special Autonomy Fund is unable to significantly reduce poverty levels in Aceh. The key point is that the Special Autonomy Fund is not pro-poor budgeting and is failing to address the poverty problem in Aceh.